Justo meio entre os excessos: a obra política do Visconde de Cairu - Stinguel, Marcela Portela (2018)
This study aims to reflect on the life and work of José da Silva Lisboa, the Viscount of Cairu, a Brazilian scholar who worked in the late the 18th century and early 19th century. In order to do so, we explored the contemporary events that formed the contexto of intellectual production and political action in Brazil. The proposed section for this dissertation is limited to the years between 1756 and 1835, which correspond to the birth and death of Silva Lisboa, respectively. By researching about this Brazilian and his attitude as a man linked to power, the books published by him will be verified so that there is a better understanding of his real collaborations for the construction of the Brazilian Empire.